Penerapan Model Pembelajaran Kooperatif Tipe Learning Together (LT) dengan Pendekatan Konstruktivis untuk Meningkatkan Aktivitas Belajar Siswa Kelas X IIS 5 SMA Negeri 1 Malili (Studi pada Materi Pokok Ikatan Kimia) - Andi Taufiq Umar (Jurusan Kimia FMIPA UNM, 2020)
Classroom action research (PTK) is intended to determine how to implement the step by step of Learning Together through Constructivist approach to improving student learning activities Class X IIS 5 SMA Negeri 1 Malili, Kab. Luwu Timur. Broadly speaking there are four stages in the PTK, namely (1) the action plan, (2) implementation (3) observation, and (4) reflection. This research was conducted as much as two cycles. Data results showed that the learning Leaning Together with the constructivist approach can enhance students' learning activities Class X IIS 5 SMA Negeri 1 Malili, Kab. Luwu Timur which consists of 6 phases: (1) a preliminary phase by providing apersepsi of matter and learning objectives, (2) phase of presentation of the material with a general presentation of the learning material so that begs the question (to observe and ask), (3) the phase of discussion with directing students to find solutions to problems that have been presented on the basis of LKPD and textbooks (reasoning and collecting data), (4) the percentage of the group phase by providing the opportunity for students to present the results of their discussion (communicate), (5) the award phase to give praise and prizes for students and groups are viable and active during discussions and the percentage of the group to improve the students' enthusiasm for learning, and (6) phase concluded by describing the conclusions of the solution to the problem which is the basis of learning activities. The percentage of student activity increased by 28.20%. The average value of student learning outcomes, namely a percentage 85.24 with mastery learning outcomes increased by 59.52%.